Prognostic score for recurrence after Whipple's pancreaticoduodenectomy for ampullary carcinomas; results of an AGEO retrospective multicenter cohort. Issue 4 (April 2015) - Colussi, O.; Voron, T.; Pozet, A.; Hammel, P.; Sauvanet, A.; Bachet, J.B.; Vaillant, J.C.; Rougier, Ph.; Nordlinger, B.; Berger, A.; Coriat, R.; Dousset, B.; et al.
Abstract Background Ampullary carcinoma (AC) is a relatively rare entity often managed as a biliopancreatic carcinoma. AC has a better prognosis than peri ampullary tumors after resection, but more than a third of patients relapse. Factors predictive of recurrence are controversial, mainly because the relevant studies are very small or also included non AC tumors. There are no guidelines on the use of adjuvant or neoadjuvant chemotherapy. The aim of this study was to identify prognostic factors for recurrence after AC resection in a large multicentric cohort, and to establish a simple, practical, predictive score for recurrence in order to guide multidisciplinary decisions. Methods We included 152 consecutive patients who underwent Whipple's pancreaticoduodenectomy for ampullary carcinoma from January 2000 to December 2010 in 10 gastrointestinal oncology departments. Results The estimated overall 5-year disease-free survival rate (DFS) was 47.1%. In multivariate analysis, age≥ 75 years at diagnosis (p < 0.0001), poor general condition (p = 0.01), poorly (p = 0.005) or moderately differentiated tumors (p = 0.01) and TNM stage IIb or III (p = 0.05) were associated with poor DFS. Based on this multivariate analysis, we developed a prognostic score with three levels of risk: DFS at 5 years was 73.5% in the low-risk group and 20.1% in the high-risk group. Conclusion This simple score based on age, general condition, tumor differentiation and TNM stage can classify patients into subgroups with different risks of recurrence and could help with therapeutic decisionmaking.